Pengaruh Word Of Mouth Terhadap Keputusan Pembelian Pada Konsumen Angkringan Cahsaiki Bekasi - Rizkika Nur Arafah; Subali Subali (Jurnal Pendidikan Ekonomi (JUPE), 2023)
This research was conducted aiming to analyze whether there is influence of word of mouth on product purchasing decisions for Angkringan Cahsaiki Bekasi consumers. Where the independent variable, namely Word Of Mouth (X), affects the Purchase Decision (Y) as the dependent variable. The population in this study were Angkringan Cahsaiki Bekasi consumers with a sample of 140 respondents through the distribution of research questionnaires filled in by the respondents. Then the data obtained were analyzed using simple regression analysis. This analysis includes validity test, reliability test, simple regression analysis, t-test, and analysis of the coefficient of determination (RÂ²). Based on statistical data analysis, the indicators in this study are valid and the variables are reliable. In the normality test normally distributed. Testing the hypothesis using the t-test shows that the word of mouth variable is proven to significantly influence the dependent variable in purchasing decisions. Purchasing decision variable can be explained by word of mouth, the rest is explained by variations of other independent variables that are not included in the researcher's simple linear regression model.